2015
DOI: 10.1186/s12888-015-0678-4
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evidence about recovery and mental health

Abstract: BackgroundTwo discourses exist in mental health research and practice. The first focuses on the limitations associated with disability arising from mental disorder. The second focuses on the possibilities for living well with mental health problems.DiscussionThis article was prompted by a review to inform disability policy. We identify seven findings from this review: recovery is best judged by experts or using standardised assessment; few people with mental health problems recover; if a person no longer meets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(143 citation statements)
references
References 93 publications
(71 reference statements)
7
130
0
6
Order By: Relevance
“…In accordance with the altered perspective of the participants in this study, a broader view on recovery can be noticed in the organisation of (mental) health care: a dichotomous understanding of “health” versus “illness” is increasingly replaced by a definition of “positive health” (Delespaul et al, 2016; Huber et al, 2011; Slade & Longden, 2015). The latter emphasizes the possibilities and abilities, given psychological, physical and social challenges and is considered more in line with clinical practice (Delespaul et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…In accordance with the altered perspective of the participants in this study, a broader view on recovery can be noticed in the organisation of (mental) health care: a dichotomous understanding of “health” versus “illness” is increasingly replaced by a definition of “positive health” (Delespaul et al, 2016; Huber et al, 2011; Slade & Longden, 2015). The latter emphasizes the possibilities and abilities, given psychological, physical and social challenges and is considered more in line with clinical practice (Delespaul et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…This is consistent with a recovery-oriented understanding of voice-hearing. 45 Indeed, a similar ability to control voice-hearing was first reported by Romme and Escher in their survey of non-help-seeking voice-hearers. 21 Furthermore, anthropological studies of voice-hearing in small face-to-face societies found that shamans, spiritual practitioners who work for the good of the group by channeling metaphysical powers, also maintained a degree of control over their experiences.…”
Section: Discussionmentioning
confidence: 80%
“…Beyond stigma, many people diagnosed with psychosis report that the diagnosis itself, especially when provided by institutions which appear to embrace stigma, is experienced as invalidating their potential identity and as an effort to control them in a paternalistic manner [150][151][152] . Indeed, independent studies have reported that clinical insight and stigma interact in a manner that results in the experience of reduced meaning 153 and self-clarity in life 154 .…”
Section: Social and Political Factors As A Root Of Poor Insightmentioning
confidence: 99%